Active Site Mapping of Human Cathepsin F with Dipeptide Nitrile Inhibitors. Issue 8 (26th June 2015) - Schmitz, Janina; Furtmann, Norbert; Ponert, Moritz; Frizler, Maxim; Löser, Reik; Bartz, Ulrike; Bajorath, Jürgen; Gütschow, Michael
Abstract Cleavage of the invariant chain is the key event in the trafficking pathway of major histocompatibility complex class II. Cathepsin S is the major processing enzyme of the invariant chain, but cathepsin F acts in macrophages as its functional synergist which is as potent as cathepsin S in invariant chain cleavage. Dedicated low‐molecular‐weight inhibitors for cathepsin F have not yet been developed. An active site mapping with 52 dipeptide nitriles, reacting as covalent–reversible inhibitors, was performed to draw structure–activity relationships for the non‐primed binding region of human cathepsin F. In a stepwise process, new compounds with optimized fragment combinations were designed and synthesized. These dipeptide nitriles were evaluated on human cysteine cathepsins F, B, L, K and S. Compounds 10 (N‐(4‐phenylbenzoyl)‐leucylglycine nitrile) and 12 (N‐(4‐phenylbenzoyl)leucylmethionine nitrile) were found to be potent inhibitors of human cathepsin F, with Ki values <10 nM. With all dipeptide nitriles from our study, a 3D activity landscape was generated to visualize structure–activity relationships for this series of cathepsin F inhibitors.